Handbook of ICU therapy - Fuller, John; Granton, Jeff; McConachie, Ian (Cambridge : Cambridge University Press, 2014)
This popular handbook provides a practical guide to managing common and important problems in the critically ill patient, as well as sufficient background information to enable understanding of the principles and rationale behind the therapy without overloading the reader with detailed basic science. Fully updated throughout, this third edition of Handbook of ICU Therapy includes new chapters on coagulation problems in the critically ill, airway management, electrolyte and metabolic acid/base problems, optimizing antimicrobial therapy, chronic critical illness, recognizing and responding to the deteriorating patient, ICU rehabilitation, palliative care, neurotrauma, the comatose patient, the obstetric patient, endocrine problems, and care of organ donors. Authored by senior clinicians from both sides of the Atlantic, chapters retain the easy-to-read format of previous editions. Aimed particularly at residents and trainees starting out in the ICU or preparing for postgraduate examinations, this handbook also serves as a valuable refresher for established intensivists, anesthesiologists and surgeons.
Title from publisher's bibliographic system (viewed on 13 May 2016).